2018
DOI: 10.1007/s00737-018-0831-4
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of bipolar disorder during pregnancy: a systematic review

Abstract: We conducted a systematic review of the literature to determine the prevalence of mood episode recurrences during pregnancy among women with bipolar disorder. Included studies (n = 11) had wide variation in the reported proportions of pregnant women with bipolar disorder who experienced a recurrence (median = 24%, range = 4-73%). There is some evidence that pregnant women are more likely to have a depressive or mixed episode, rather than hypomanic or manic. The extant literature cannot answer the question of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…Around 10‐20% of pregnant women with prior depression seem to experience a depressive relapse, but with a broad range of estimates (from <5% to 75%) 24,25 . For bipolar disorder, a systematic review of 14 mainly small studies (including a total of 2,345 women, but with only two studies with a sample size of >100) suggests that around one in five women experience a relapse during pregnancy 24 , with a possible predominance of depressive and mixed episodes (in contrast to prominent manic episodes in the postnatal period) 5,24,25 . However, a recent electronic health record study reported a relapse rate of 10% 26 , possibly reflecting different populations.…”
Section: Prevalence Of Mental Disorders In the Perinatal Periodmentioning
confidence: 99%
“…Around 10‐20% of pregnant women with prior depression seem to experience a depressive relapse, but with a broad range of estimates (from <5% to 75%) 24,25 . For bipolar disorder, a systematic review of 14 mainly small studies (including a total of 2,345 women, but with only two studies with a sample size of >100) suggests that around one in five women experience a relapse during pregnancy 24 , with a possible predominance of depressive and mixed episodes (in contrast to prominent manic episodes in the postnatal period) 5,24,25 . However, a recent electronic health record study reported a relapse rate of 10% 26 , possibly reflecting different populations.…”
Section: Prevalence Of Mental Disorders In the Perinatal Periodmentioning
confidence: 99%
“…Previous studies suggested that women with bipolar disorder may have a lower risk of relapse during pregnancy, when compared to the period before or after (Grof et al 2000). A recent systematic review concluded that based on the literature to date the question of how pregnancy affects the course of bipolar disorder can’t be answered (Salim et al 2018). Viguera et al showed that in women who discontinued mood stabilizing treatment including lithium during pregnancy (n = 62), the relapse risk was two times increased compared to women who continued treatment (n = 27) (Viguera et al 2007).…”
Section: Lithium During Pregnancymentioning
confidence: 99%
“…Dentre as particularidades de cada classe de 12,13 . Tenta-se preconizar a administração de medicamentos, durante a gravidez ou aleitamento materno, somente quando são necessários e em menor período possível.…”
Section: Discussionunclassified